Avaliação de diferentes misturas de extratantes comerciais aplicadas à purificação de ácido fosfórico industrial - Sebastião Ailton Rodrigues (2011)
A rationalized evaluation of phosphate deposits shows a trend of P2O5 grade reduction along with a resulting increase in contaminants in new ore bodies that are found around the globe. For that reason, breakthrough purification processes need to be developed to properly refine the produced phosphoric acid, even fertilizer grade. Solvent extraction has been applied to phosphoric acid purification applying organic extractants with different functional groups, such as ethers, alcohols, ketones, esters, trialquilphosphates and amines. These extractants can be evaluated separately or in synergistic mixtures that could bring, among other benefits, more efficient phase separation. The present work has evaluated the following commercial extractants, isolated or in synergisticmixtures, for industrial phosphoric acid purification: Tributyl Phosphate (TBP), Di-Isopropyl Ether (EDIP), Metil-Isobutyl Ketone (MIBK), Alamine 336, Hexanol and Heptanol. It was found that EDIP and TPB are the most suitable extractants for purification of the specific industrial phosphoricacid that was the focus of this study, but relatively high sulphate and fluorine extractions were also seen. In order to avoid that contamination, an efficient pre-treatment stage is critical. Use of alcohols is also an alternative for inhibiting both sulphate and fluorine extractions, but can also result in lower phosphorous recoveries, that can be compensated by a higher organic/aqueous ration. Usage of amines is not beneficial, as it extracts impurities and deteriorates phase separation. Temperature reduction did not bring any particular benefits to the process. It was also confirmed that an improvement in analytical methodology is needed, especially applied to impurity determination in concentrated phosphoric acid solutions, right after a solvent extraction operation